Canopy temperature and heat use efficiency of spring maize under modified soil microenvironment - Majumder, Debjyoti; Kingra, P.K.; Kukal, S.S. (Annals of Agricultural Research, 2016)
A field experiment was conducted to assess the canopy temperature and heat use efficiency ofmaize (var. PMH-7) under modified soil micro environment during spring 2014 at the ResearchFarm, Punjab Agricultural University, Ludhiana. The experiment was laid out in factorial randomizedblock design comprising three irrigation levels (IW/CPE = 1.25 (I1), 1.0 (I2) and 0.75 (I3)) and fourmanuring treatments (surface manurng (S), sub-surface manuring (DF), digging alone (D) and control(C). Higher canopy temperature was observed under the I3 followed by I2 and I1, whereas undermanuring treatments, higher temperatures were observed under control (C), followed by digging(D), surface (S) and sub-surface manuring (DF), respectively. Crop took 127 days to complete its lifecycle and accumulated 5062.3°C day growing degree days (GDD), 45795.3°C day hour heliothermalunits (HTU) and 64664.7°C day hour photothermal units (PTU). The regression analysis depictedpositive relation of heat use efficiency with maximum leaf area index (R2 = 0.61), dry matterproduction (R2 = 0.97) and grain yield (R2 = 0.55) under different irrigation and manuring treatments.The regression analysis between canopy temperature and grain yield under different treatmentsshowed negative relation indicating a decrease in grain yield of maize by 2.8 q/ha with increase incanopy temperature by 1°C. The study highlights the negative impact of global warming on cropproductivity and significance of microclimatic modifications viz. irrigation scheduling and subsurfacemanuring in managing canopy temperature and heat use efficiency of spring maize underchanging climatic conditions.